5G Rollout Planning at Frequency 3.5 GHz: Study Case in Ibu Kota Negara - Amran Paso Salmeno; David Eka Putra (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2026)
In tropical countries where the rainfall intensity is constantly high, the 3.5 GHz band is a valuable spectrum for the fifth generation (5G) broadband implementation. That is because it provides a balanced trade-off between high capacity and resilience to rain attenuation in tropical climates. However, deploying this band faces regulatory, legal, and technical constrains, especially related to legacy spectrum allocation. This work focuses on key challenges in deploying 3.5 GHz band for 5G network in Indonesia, including regulatory, legal, and technical factors. Indonesia’s new capital city, Ibu Kota Negara (IKN), a smart city with a population projection of 1.9 million by 2045, is used as a case study. A quantitative network planning approach is applied to evaluate coverage and capacity, resulting in an estimated cell radius of 992.4 m, a requirement of approximately 245 gNodeBs, and a total offered throughput of 16.49 Tbps. We analyze the implication of mid-band spectrum characteristics and regulatory limitations on the network deployment planning. The findings are expected to provide a better understanding in spectrum management and network planning, particularly in developing new smart cities.